Implanted antennas - Mohammed Hisham Hassan; Abdelmegid Mahmoud Allam (Cairo : Mohammed Hisham Hassan, 2013)
Wireless technology has been a growing one through the past few decades, with this rapid growth; different types of antennas have been introduced to meet certain requirements. These intoduced antennas are microstrip patch, planar inverted L - F, planar dipoles monopoles, and suspended plate. A person's health is one of the most basic fundamentals in life
Thesis (M.Sc.) - German University - Faculty of Postgraduate Studies and Scientific Research - Department of Communications